Eksplorasi Penggunaan Teknologi Blockchain dalam Transaksi Keuangan Syari'ah BSI KCP Probolinggo - Mohammad Ali Ma’ruf; Muhammad Hifdil Islam; Hayatul Millah (Masyarakat Ekonomi Syariah Bogor, 2024)
This research explores the potential and challenges of using blockchain technology in Islamic financial transactions. Blockchain is known for its ability to increase transparency, security and efficiency in recording transactions, which is in accordance with sharia financial principles. This research uses a qualitative approach with a literature review method to examine relevant literature from various academic and practical sources. The research results show that blockchain technology has great potential to increase transparency, efficiency and sharia compliance in financial transactions. Blockchain also offers potential applications in the management of waqf and zakat, as well as in the development of peer-to-peer (P2P) lending and sharia crowdfunding platforms. However, the implementation of this technology faces several challenges, including sharia regulation and compliance, technology adoption and acceptance, and security and scalability issues. This research provides recommendations for overcoming these challenges, including collaboration between regulators, sharia scholars, and technology developers, as well as increasing education and training about blockchain among sharia finance practitioners. With effective adoption and in accordance with sharia principles, blockchain technology can support the development of more innovative and sustainable sharia finance.